2022
DOI: 10.1149/10701.10785ecst
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Bilingual Mode of Instructional Design for Higher Education

Abstract: Immersion in English language at higher education level might not benefit students who did their schooling in their mother tongue, native tongue, or regional language. L2 classroom is the only way for the students who come from economically and socially backward communities to learn the language. When the instruction is fully in English, these students feel left out and disconnected. They are not motivated enough as the means to attain goals is not clear. Therefore, it is hypothesized that a bilingual mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…For instance, Ashraf (2023) and Asif et al (2022) also found an effect of the first language on attitudes towards research activities. Furthermore, prior studies on the impact of first language on attitudes towards doing research projects also confirm H1 (Edmon & Hema, 2022;Fernández & Julius, 2017;García & Wei, 2014). Hence, the results reinforce the significance of the first language in the research process because it can significantly influence students' attitudes towards doing research projects.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…For instance, Ashraf (2023) and Asif et al (2022) also found an effect of the first language on attitudes towards research activities. Furthermore, prior studies on the impact of first language on attitudes towards doing research projects also confirm H1 (Edmon & Hema, 2022;Fernández & Julius, 2017;García & Wei, 2014). Hence, the results reinforce the significance of the first language in the research process because it can significantly influence students' attitudes towards doing research projects.…”
Section: Resultssupporting
confidence: 73%
“…While there is evidence to support the notion that bilingual competence can positively influence attitudes towards doing research projects, it is critical to keep in mind that the relationship between these variables is likely to be nuanced and context-dependent (Chen, He, & Fan, 2022;Edmon & Hema, 2022;Kanwal et al, 2022). More empirical research is needed to fully understand the impact of bilingual competence on attitudes towards doing research projects (Valizadeh & Gunday, 2022).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%